Yearly Fluctuations in Honey Production in Hokkaido, Northern Japan, with Special Reference to Weather Conditions and Masting Behavior - Masaka, Kazuhiko (International Journal on Food, Agriculture and Natural Resources, 2023)
The factors controlling yearly fluctuations in honey production are poorly understood. To evaluate yearly fluctuations in honey production, the coefficient of variation (CV) and the autocorrelation analysis were used to determine the magnitude and periodicity of the fluctuations for seven major nectar-source plants (basswood, black locust, Amur cork tree, white clover, buckwheat, Kamchatka thistle, and horse chestnut) using 15-years of data obtained in Hokkaido, Japan. Regression analysis was conducted to evaluate the relationship between annual honey production and the corresponding weather conditions during the flowering month. The periodic synchronous flowering and fruiting observed in tree species is called masting or masting behavior. A masting model, based on the resource budget, was applied to tree species if periodicity was detected by an autocorrelation analysis. The CV differed markedly among species. Black locust and the Amur cork tree had the smallest and largest CVs, respectively, whereas basswood was periodic. A negative correlation was observed between monthly precipitation and honey production in black locust, white clover, thistle and the Amur cork tree. This result implies that rain inhibits honey bee foraging. Production of buckwheat honey, however, tended to increase with increasing mean temperature. It might be difficult to detect the effect of rain on the honey production using buckwheat presumably because of the long flowering period. Annual honey production in basswood could be described by the resource budget model, but not in horse chestnut. Some horse chestnut trees produce flowers even in non-mast year implying that it was difficult to detect the periodicity in this species. According to beekeepers, honey production in this last decade in Hokkaido has been disrupted by climate change and the transitioning of the industrial structure.